Steinbeck Center room - Doctor Paul Douglass:::Creator::::::::::::
Martha Heasley Cox Center for Steinbeck Studies in its forth location, on the 5th floor of the Doctor Martin Luther King, Junior Library. Digital copy only. No hard copy.